Learning Pressure and Students’ Academic Achievement a Quanitative Study of Fifth-Grade Students’ at SDN 064025 - Elisabeth Rose Galingging; Novia Br Manik; Medianti simanjuntak (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
Learning pressure is one of the psychological factors that may influence students’ concentration, motivation, emotional condition, and academic achievement. At the elementary school level, students may experience learning pressure from school assignments, examinations, parental expectations, teacher demands, peer competition, and fear of failure. This study aims to examine the influence of learning pressure on students’ academic achievement among fifth-grade students at SDN 064025 in the 2023/2024 academic year. This study employed a quantitative approach. The participants were 22 fifth-grade students. Data were collected using a learning pressure questionnaire and an academic achievement test. The instruments were tested through item validity and reliability analysis. The learning pressure questionnaire initially consisted of 10 items, with 6 valid items and 4 invalid items based on the validity test. The academic achievement test consisted of 20 items, with 12 valid items and 8 invalid items. The reliability test showed that the learning pressure questionnaire had a Cronbach’s alpha of 0.570, while the academic achievement test had a Cronbach’s alpha of 0.788. The normality test using the Kolmogorov-Smirnov test showed a significance value of 0.200, indicating that the residual data were normally distributed. The regression result showed that learning pressure had a negative but statistically non-significant effect on students’ achievement, with B = -0.284, t = -0.300, and p = 0.767. This finding indicates that learning pressure was not a significant predictor of students’ academic achievement in this sample. The study concludes that although excessive learning pressure may theoretically interfere with students’ learning, the data in this study did not provide sufficient statistical evidence to prove a significant effect.